2020
DOI: 10.1186/s10020-020-00161-7
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-regulated PTTG1 promotes breast cancer progression by regulating cyclin kinase expression

Abstract: Background The present study aims to investigate the effects of pituitary tumor transforming gene (PTTG) 1 on breast cancer and its underlying mechanism. Methods GEO data set was applied to analyze the relationship between PTTG1 and survival status and the TCGA breast cancer dataset was used to explore its possible targets. The stable cell lines including PTTG1 knockdown cells, estrogen receptor (ESR) 1 knockdown cells, and PTTG1 overexpression cells were constructed. MTT was used to determine cell viabilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 28 publications
2
20
0
Order By: Relevance
“…A previous study reported that PTTG1, an overexpressed gene in seminoma tumor, promoted the migration and invasion of tumor cells via activation of MMP-2 [ 25 ]. In addition, the prognostic values of PTTG1 were also reported in several tumors, such as breast carcinoma and prostate carcinoma [ 8 , 26 ]. According to the findings above, PTTG1 is an oncogene in the above tumors.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that PTTG1, an overexpressed gene in seminoma tumor, promoted the migration and invasion of tumor cells via activation of MMP-2 [ 25 ]. In addition, the prognostic values of PTTG1 were also reported in several tumors, such as breast carcinoma and prostate carcinoma [ 8 , 26 ]. According to the findings above, PTTG1 is an oncogene in the above tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Acid ceramidase (ASAH1) can upregulated the CCNB2 expression and promote BC cell proliferation [46]. Meng et al reported that PTTG1 was overexpressed in BC and might target CCNB2, resulting in more BC cells distributed in S phase [47]. To date, there is no report revealing the expression level of CCNB3 in BC and predicting the prognostic value for BC patients.…”
Section: Discussionmentioning
confidence: 99%
“…For example, PTTG1 has been implicated in breast cancer development through regulation of the epithelial-mesenchymal transition (EMT) and functions of p27 and RhoA signaling ( Quereda and Malumbres, 2009 ; Yoon et al, 2012 ; Lim et al, 2016 ). In addition, estrogen has been shown to promote breast cancer development through increasing PTTG1 expression ( Chen et al, 2017 ; Meng et al, 2020 ). Although many studies have demonstrated the roles of overexpressing PTTG1 in breast cancer metastasis, the mechanisms underlying regulation of PTTG1 expression are still unclear.…”
Section: Discussionmentioning
confidence: 99%